Implementasi Sistem Penerangan Jalan Menggunakan Lampu Sonar Panel Cell RT 58 Kelurahan Sepinggan Balikpapan Selatan - Ikmaluddin Ikmaluddin (Lembaga Pengembangan Kinerja Dosen, 2025)
Roads are the main infrastructure that supports human life. When the infrastructure in the form of roads is good, then all community activities, from the economy, transportation, to equitable development can also be realized well. Sepinggan, South Balikpapan District, Balikpapan City is one of the cities in East Kalimantan whose road infrastructure is quite adequate. However, there is a road that does not have maximum lighting at night. Apart from poor visibility and increasing the risk of accidents, it also risks attracting crime. Therefore, members of the Balikpapan University KKN 2024 made street lighting at Posyandu Kusuma RT 58. The street lighting was made with solar power. Solar powered street lighting was chosen to maximize power efficiency. The methods used in these activities are identification, implementation, and achievements or outputs of activities. The people of RT 58 really appreciate the making of solar panel lights carried out by the 2024 Balikpapan University KKN team. The community's activities at night when passing through roads that already have cell panel lights become more optimal and productive.